Venom [videorecording (DVD)] - Hardy, Tom, 1977-; Williams, Michelle, 1980-; Ahmed, Riz, 1982- (Sony Pictures Home Entertainment, 2018)
Investigative journalist Eddie Brock attempts a comeback following a scandal, but accidentally becomes the host of an alien symbiote that gives him a violent super alter-ego. Soon, he must rely on his newfound powers to protect the world from a shadowy organization looking for a symbiote of their own.